Angioplasty for renovascular hypertension in 78 children. Issue 5 (19th December 2014) - Kari, Jameela A; Roebuck, Derek J; McLaren, Clare A; Davis, Meryl; Dillon, Michael J; Hamilton, George; Shroff, Rukshana; Marks, Stephen D; Tullus, Kjell
Abstract : Objectives: To evaluate the outcome of percutaneous transluminal angioplasty (PTA) in children with renovascular hypertension (RVH) treated at a single centre over 29 years. Methods: A retrospective study of the medical charts of all children with RVH who underwent PTA between 1984 and 2012. The primary outcome measurement was blood pressure (BP) achieved after the procedure. The BP before the procedure was compared with that at last available follow-up, 6 (range 0.6–16) years after the initial procedure. Results: Seventy-eight children with median (range) age of 6.5 (0.5–17) years were studied. Twenty-three (29.5%) had an underlying syndrome, 35 (44.9%) children had bilateral renal artery stenosis (RAS), 18 (23%) intrarenal disease and 11(14%) showed bilateral RAS and intrarenal disease. Twenty (25.6%) children had mid-aortic syndrome and 14 (17.9%) cerebrovascular disease. One hundred and fourteen PTA procedures were carried out including 31 stent insertions. Following PTA, BP was improved in 49 (62.8%) children and of those 18 (23.1%) were cured. Children with involvement of only the main renal arteries showed improved BP control in 79.9% of the children with cure in 39.5%. BP was intentionally maintained above the 95th centile for age and height in four children with coexistent cerebrovascular disease. No change in BP was seen in 18 children despite observed technical success of the PTA, and in seven children due to technical failure of the procedure. Conclusions: PTA provided a clinical benefit in 62.8% of children with RVH.